Persistence of hSBA titers elicited by the meningococcal serogroup B vaccine menB-FHbp for up to 4 years after a 2- or 3-dose primary series and immunogenicity, safety, and tolerability of a booster dose through 26 months - Østergaard, Lars; Vesikari, Timo; Senders, Shelly D; Flodmark, Carl-Erik; Kosina, Pavel; Jiang, Han-Qing; Maguire, Jason D; Absalon, Judith; Jansen, Kathrin U; Harris, Shannon L; Maansson, Roger; Balmer, Paul; et al. (Vaccine, 2021)
BACKGROUND: To demonstrate extended protection against meningococcal serogroup B (MenB) disease after MenB-FHbp (bivalent rLP2086) vaccination, this study evaluated immunopersistence through 26 months following MenB-FHbp boosting after 2 or 3 primary doses in adolescents. STUDY DESIGN: This phase 3, open-label study was an extension of 3 phase 2 studies with participants aged 11-18 years randomized to receive primary MenB-FHbp vaccination following 1 of 5 dosing schedules or control. A booster dose was administered 48 months after the primary series. Immunopersistence through 48 months after the last primary dose (persistence stage) and 26 months postbooster (booster stage) was determined by serum bactericidal assays using human complement (hSBAs) against 4 vaccine-heterologous test strains. Safety evaluations included adverse events (AEs) and local and systemic reactions. RESULTS: Overall, 698 and 304 subjects enrolled in the persistence and booster stages, respectively. hSBA titers declined in all groups during 12 months postprimary vaccination, then remained stable through 48 months. One month postbooster, 93.4-100.0% of subjects achieved hSBA titers ≥ lower limit of quantitation against each test strain; percentages at 12 and 26 months postbooster were higher than at similar time points following primary vaccination. Primary and booster MenB-FHbp vaccinations were well tolerated, with ≤ 12.5% of subjects reporting AEs during each stage. The most common local (reported by 84.4-93.8% of subjects) and systemic (68.8-76.6%) reactions to the booster were injection site pain and fatigue and headache, respectively; ≤ 3.7% of subjects reported severe systemic events. CONCLUSION: Protective hSBA titers initially declined but were retained by many subjects for 4 years irrespective of primary MenB-FHbp vaccination schedule. Boosting at 48 months after primary vaccination was safe, well tolerated, and induced immune responses indicative of immunological memory that persisted through 26 months. Booster vaccination during late adolescence may prolong protection against MenB disease.
Keywords: imunogenicita vakcíny; Antibodies, Bacterial; protilátky bakteriální; Meningococcal Infections; lidé; Serogroup; Humans; Meningococcal Vaccines; Immunogenicity, Vaccine; meningokokové infekce; mladiství; meningokokové vakcíny; Neisseria meningitidis séroskupiny B; Adolescent; séroskupina; Neisseria meningitidis, Serogroup B